2014
DOI: 10.1186/2193-1801-3-301
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of the compound cis-tetraammine(oxalato)ruthenium(III) dithionate on K-562 human chronic myelogenous leukemia cells

Abstract: Chemotherapy is a common treatment for leukemia. Ruthenium complexes have shown potential utility in chemotherapy and photodynamic therapy. The identification of new chemotherapeutics agents is critical for further progress in the treatment of leukemia. Ruthenium complexes generally have lower toxicities compared to cisplatin attributed to their specific accumulation in cancer tissues. Based on these evidences, in the present work we studied the cytotoxic activity of the ruthenium(III) compound cis-tetraammine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…The data analysis points out no significant differences in cell death between the PBMC, MCF-7, PBMC + modified Ru (III) complex (Incentive) groups and that the rate is similar and low. Furthermore, studies carried out by Tarso [16] indicated that ruthenium compounds as identical in the structure had similar effects to those observed here, that is, that statistically, the stimuli tested do not have toxic effects on cells used. However, when the analysis is restricted to MCF-7 + Incentive, the data showed significant differences, showing considerable toxicity to this strain.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The data analysis points out no significant differences in cell death between the PBMC, MCF-7, PBMC + modified Ru (III) complex (Incentive) groups and that the rate is similar and low. Furthermore, studies carried out by Tarso [16] indicated that ruthenium compounds as identical in the structure had similar effects to those observed here, that is, that statistically, the stimuli tested do not have toxic effects on cells used. However, when the analysis is restricted to MCF-7 + Incentive, the data showed significant differences, showing considerable toxicity to this strain.…”
Section: Resultssupporting
confidence: 84%
“…From this discovery, some compounds derived from Ru +3 and Ru +2 with amine [12] coordinated to N-heterocyclic ligands [13] [14] and alkyl sulfoxide ligand ligands [15] have also demonstrated a potential antimetastatic activity. In addition, new studies based on ruthenium [16] [17] [18] [19] have become the target of numerous therapeutic studies being applied in the fight against cancer. These properties cited above prompted us to make a new ruthenium-derived compound and test its antitumor potential.…”
Section: Introductionmentioning
confidence: 99%
“…Metals with anti-cancer properties such as gold, silver, platinum, or ruthenium can be coordinated with the terminal surface groups [11,13,15]. Ruthenium seems particularly interesting because it can exist in various oxidation states, among which Ru(II) is strongly cytotoxic [11,16]. In addition, ruthenium resembles iron and can be similarly attached to transferrins and albumins [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Because of their rapid metabolism and increased demand for iron, cancer cells can take up ruthenium instead of iron [17,18]. Moreover, ruthenium atoms can perturb DNA replication in tumor cells, leading to cell death [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…1a,b), anterior capsulectomy was accomplished by cutting with a 25G vitreous cutter inserted from a corneal limbal side‐port under continuous irrigation with a 25G infusion cannula also inserted from another limbal side‐port, as done in congenital cataract surgery in human eyes 30. At vitrectomy 25, retinal detachment (retinal bleb) was successfully induced in the area with retinal degeneration by subretinal injection of intraocular irrigating solution with a 38G polyimide tip (Fig.…”
Section: Methodsmentioning
confidence: 99%